The devil wears scrubs eaudiobook A short comedic novel. - McFadden, Freida (Tantor Audio, 2017)
Newly minted doctor Jane McGill is in hell. Not literally, of course. But between her drug addict patients, sleepless nights on call, and battling wits with the sadistic yet charming Sexy Surgeon, Jane can't imagine an afterlife much worse than her first month of medical internship at County Hospital. And then there's the devil herself: Jane's senior resident Dr. Alyssa Morgan. When Alyssa becomes absolutely hell-bent on making her new interns pay tenfold for the deadly sin of incompetence, Jane starts to worry that she may not make it through the year with her soul or her sanity still intact.